Real-time multi-sensors measurement system with temperature effects compensation for impedance-based structural health monitoring - Baptista, Fabricio G.; Vieira Filho, Jozué [UNESP]; Inman, Daniel J. (Sage Publications Ltd, 2012)
This article presents a simple and versatile measurement system for structural health monitoring (SHM) based on the electromechanical impedance (EMI) technique. The proposed system allows real-time data acquisition from multiple sensors and includes compensation for temperature effects, eliminating one cause of incorrect diagnoses in structural monitoring. Besides the low cost compared to conventional impedance analyzers, the hardware and the software are simple and easier to implement than other measurement systems that have been recently proposed. Tests were carried out on an aluminum beam under different temperatures and on an aluminum plate with nine PZT (lead zirconate titanate) patches. The experimental results show conclusively that the proposed methodology is efficient and feasible for real-time SHM.
Keywords: structural health monitoring; SHM; damage detection; piezoelectric transducers; PZT; electromechanical impedance; measurement system